THE EFFECT OF STORYTELLING METHODS ON THE ABILITY OF OWNING EARLY CHILDREN (Literasi Nusantara, 2022)
This study aims to determine the effect of storytelling methods on listening ability in children aged 5-6 years in TK Tunas Harapan Batokan. The purpose of this study was to test the hypothesis of the storytelling method on children's listening ability. This research method is pre-experimental design with the type of One-Group Pre-test Post-test Design. The sample of this study was 15 children (7 boys and 8 girls). The data collection techniques used were observation and documentation. The data analysis technique used statistics with t-test with SPPS 16.0 program. Hypothesis testing is done using t-test with thetechnique Independent T-test, obtained tcount of 0.000 at the significance level ???? 0.05. This proves that the storytelling method affects children's listening ability.
Keywords: Listening; Ability; Storytelling; Method